Sense-making - Boyle, Sheryl (Sensory architecture director), author.
1 online resource (302 pages)
Keywords: In this highly innovative work, the senses are liberated from the confines of the present to serve as vehicles for accessing other historical periods and imagined futures. Sense-Making builds on the burgeoning field of sensory ethnography by introducing a pair of methodologies-sensory (re)construction and sensorial extrapolationCexpressly devised to facilitate time-travel.The first part offers a survey and critique of extant work in sensory archeology and sensory futures. The second part presents a case study of sensory (re)construction in action, focusing on Thornbury Castle (1508-1521) in the UK. The third part probes the life of the senses on the "final frontier", the "next habitat" of humanity-namely, outer space. These sensory case studies are not purely architectural or purely futuristic. They are, at the same time, exercises in "arts-based practice" or "research-creation," where the authors do not just carry out bibliographic research and write about pasts and futures, they make them.Sense-Making is necessary reading for the international community of sensory studies scholars, as well as those with interests spanning material culture, museum and heritage studies, visual and auditory culture, experimental psychology, design and digital technology.